2021
DOI: 10.1002/hsr2.280
|View full text |Cite
|
Sign up to set email alerts
|

Serological identification of past and recent SARS‐CoV‐2 infection through antibody screening in Luanda, Angola

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in China and spread to the world. 1 Pneumonia caused by SARS-CoV-2 was named coronavirus disease 2019 (COVID-19) and is currently a public health concern. 2,3 From December 2019 to December 2020, more than 60.1 million cases of infection and 1.4 million deaths, have been reported worldwide. 4 Until December 2020, the Ministry of Health of Angola reported more than 15 000 cases and 345 deaths. 4 The timely diagnosis of SARS-CoV-2 infection is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
4
2
1
1
Order By: Relevance
“…The rate of SARS-CoV-2 infection increased from 0.3% in parturients under 20 to 0.4% in parturients aged 20 years and over (Table 1). These results are similar to those observed by a study carried out by our research team in the general population of Luanda, where we observed that the rate, as well as the risk of SARS-CoV-2 infection, increased with increasing age [16,17], leading to the belief that these are people who are in the active stage of life and who perform work or other activities that expose them more frequently to the virus. Our results also corroborate those of previous studies in terms of the decrease in infection (0.6% to 0.1%, p = 0.012) and risk of infection (OR: 0.18, p = 0.025) in non-urbanized to urbanized areas, respectively (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…The rate of SARS-CoV-2 infection increased from 0.3% in parturients under 20 to 0.4% in parturients aged 20 years and over (Table 1). These results are similar to those observed by a study carried out by our research team in the general population of Luanda, where we observed that the rate, as well as the risk of SARS-CoV-2 infection, increased with increasing age [16,17], leading to the belief that these are people who are in the active stage of life and who perform work or other activities that expose them more frequently to the virus. Our results also corroborate those of previous studies in terms of the decrease in infection (0.6% to 0.1%, p = 0.012) and risk of infection (OR: 0.18, p = 0.025) in non-urbanized to urbanized areas, respectively (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, other studies carried out among COVID-19 patients from China, have reported several risk factors, such as older age, male gender, and the presence of underlying chronic comorbidities with SARS-CoV-2 positivity and/or unfavorable clinical outcome among COVID-19 patients. [18,19] Also, in line with prior studies carried out by our research team in Angola [20,21], we observed an increase in SARS-CoV-2 infection rate with increasing age, men were the most affected, and the urbanized areas with the highest rate of infection (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…These measures also showed positive results in the spread of SARS-CoV-2 infection in low prevalence among the Angolan population residing in different settings, as reported by our research team in previous studies. [13][14][15][16][17] A cohort study carried out in Italy, found that about 88% of the population was fully vaccinated which was slightly low compared with the 98% rate of vaccinates observed in our study (Table 1). Also, our study presents about 10% of the unvaccinated population and there were mainly non-healthcare professionals,…”
Section: Discussioncontrasting
confidence: 66%